(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the glycemic control of people with type 2 diabetes mellitus in a Family Healthcare Unit in the city of Araras, São Paulo. This is a descriptive cross-sectional study based on the collection of sociodemographic and clinical data from physical records. 102 participants were included, 66.6% were female and mean age was 61.4 years. It was shown that 57.8% had inadequate glycemic control with glycated hemoglobin equal to or greater than 7.0%. Inadequate glycemic control was associated with age group, polypharmacy and types of medication prescribed for the treatment of diabetes (p<0.05). In diabetes pharmacotherapy, one or two medications were prescribed for 72.5% of the participants, with metformin being prescribed for 80.7%. The study showed the frequency of glycemic control, as well as the variables that influenced it, and highlights the importance of a clinical approach focused on people with diabetes in Primary Health Care in order to avoid complications resulting from the disease.